Going to the movies in VR: Virtual reality cinemas as alternatives to in-person co-viewing - Szita, Kata (My University, 2024)
Virtual reality cinemas offer computer-generated screening environments that resemble physical-world movie theaters for avatar-based viewers. Reflecting on virtual spectatorship in the context of social isolation, the present study investigates whether VR cinemas could provide an alternative for collective movie watching and whether they could facilitate an engaging experience similar to other, physical-world co-viewing environments. To measure these effects, we designed a behavioral experiment in which participants watched a feature film sequence either in VR or a physical screening room in the presence or absence of viewing companions. After viewing, participants’ experiences—including emotional engagement, narrative empathy, presence, social ex- periences, and physical and mental well-being—were recorded using survey methods. We observed that VR viewing can produce an equally enjoyable film experience, as well as similar levels of emotional engagement and narrative empathy, while it leads to increased comprehension of characters’ feelings and sense of narrative engagement. In addition, social viewing may mean less engagement and more distractions depending on the screening environment. We also found that even though previous virtual reality exposure negatively correlates with comfort and well-being during viewing, early adopters of technology and VR supporters are more likely to have an enjoyable and engaging film experience.
PUBLISHED
Keywords: Well-being; Social isolation; Narrative engagement; Audience effect; Social virtual reality; Virtual reality cinema; Neuroscience; Cognitive science; FICTION; fictionality; pretense; reality-fiction distinction; Communication